Exploration Study Of The Impact Of Working From Home (Wfh) On Employee Performance During The Covid-19 Pandemic - Pramadhi Dharma (Universitas Airlangga, 2021)
Currently, many countries around the globe including Indonesia are hugely affected by a novel pandemic COVID-19. This pandemic has impacted the economic and social sectors as well as caused dramatic changes in work patterns. Many employees are forced to shift their current working style from the office to work from home (WFH). This study aims to determine the impact of WFH on employee performance and to provide information regarding the advantages and disadvantages of WFH during the COVID-19 pandemic from the employee perspective. This exploratory study used the descriptive method and the data were obtained from the responses of 75 employees that are currently on WFH at different sectors in Surabaya. Evidently, 63% of the respondents are private employees, followed by 33% of them belongs to government employees, and 4% of employees have their state-owned enterprises. There were 83% of employees who experiences WFH due to the prevention of spreading COVID-19 transmission. The analysis of the work performance revealed that 47% of the respondents did not experience any differences between WFH and conventional office’s working style. In addition, 29% of employees expressed their opinion regarding the decrease in productivity level during WFH, and 20% of them admitted that their performance level elevated during WFH. In fact, based on the employees’ opinions, the biggest advantages of WFH include flexible working hours, efficient personal budget cuts for transportation costs, and more quality time to spend with families. However, the disadvantages of WHF are the increase in internet and electricity cost, some tasks from work that could not be performed at home such as scientific laboratory experiments, and the lack of focus to work properly due to distraction at home especially if they have their children around all time. Furthermore, even though work from home was accepted by most employees, but according to some correspondents’ opinions, the current WFH trend was not ideal for many different types of jobs.